Why Does He Do It? What Explanations Resonate During Counseling for Women in Understanding Their Partner’s Abuse? - Marsden, Sally (Journal of interpersonal violence, 2022)
Intimate partner violence (IPV) is a complex and multifaceted problem gaining increasing attention within mental health research and practice. IPV explanations focus on both individual and systemic levels; however, it is increasingly acknowledged that a single level explanation may not be sufficient. The practices of clinical disciplines may, however, still privilege an explanation at one level over another, which will influence how they work with clients. It is likely that one such clinical group, psychologists, may play a critical role in helping victim-survivors to understand and explain their experiences of IPV. However, we were unable to find any studies focusing on women?s perceptions of psychologists? role in this. Additionally, we know little about women victim-survivors? perceptions of why their partners use IPV. To address these gaps, the research question for this study was: What explanations resonate during counseling for women in understanding their partner?s abuse? To explore this question, 20 women who had seen psychologists after experiencing IPV participated in semi-structured interviews. The interviews were analyzed using reflexive thematic analysis and three themes constructed from the data. The first two themes, narcissist description was helpful and not all bad all the time, showed that the women found it powerful in their healing processes when psychologists offered the opportunity to discuss their partners individual characteristics as explanations for their use of IPV. The third theme, structural explanations, showed that some of the women also reflected on wider structural contexts. Implications for clinical practice include the potential healing effect when practitioners can move along a continuum of explanation levels, covering both the inner and outer worlds. Implications for research into IPV perpetration are that women hold expertise and insight into individual perpetrators and could make valuable contributions to this field.